Providing Arithmetic Operations on RSA using Homomorphic Technique - Shiwali,; Bhalla, Gaganpreet Kaur (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a sound area for the field of research. In the current scenario of advanced technology the client and server architecture is been shifting from distributed or cluster to cloud architecture. The main part of this research relies on robust architecture which deals with Cloud Storage as a Service (SAAS) and comparative security measures of improvement and modifications [1]. Cloud computing is the internet based technology which providing the computing resources in the form of services over the internet. But security is the main issue occurred in the cloud computing because of that growth of cloud computing is less.By using cryptography algorithms, we improve the data security in cloud computing. The cryptography algorithms are used for purpose of secure transmission of private or secret message. There are several number of cryptography algorithms but here we integrate the new technique with RSA algorithm using Homomorphic Encryption and performing the arithmetic process on RSA which improving the security level without compromising the security of existing technique [2]. In this paper our main work to ensure the security of data, so we proposed a method by implementing RSA algorithm using Homomorphic Encryption.